Optimizing Village Potential through SMEs Mapping for SDGs Achievement - Sari, Juwita; Mildawati, Titik; Reza Pahlawan, Muhammad; Respatia, Wimba; Abdullah, Rachmad (OJS Universitas Muhammadiyah Gresik, 2025)
Yosowilangun Village, located in Gresik Regency, is currently classified as an independent village, indicating the prosperity of its residents. However, there are still challenges in identifying and optimizing the village’s potential, particularly in recognizing its strengths and addressing weaknesses. Without a systematic approach to these issues, there is a risk of a decline in the village development index, potentially resulting in a downgrade of its status. The Sustainable Development Goals (SDGs) framework offers a strategic pathway for achieving balanced and sustainable growth, with its core pillars emphasizing humanity, the environment, prosperity, peace, and partnerships. In collaboration with the officials of Yosowilangun Village, Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya implemented a pilot project aimed at mapping and analyzing the village's potential. This project identified underutilized land, which has typically been used for cultural and artistic activities, as a valuable resource for local economic empowerment. By transforming this land into a venue for Small, and Medium Enterprise (SME) events, such as craft and culinary exhibitions, the village can create sustainable economic opportunities. The project also revealed that village officials allocate a significant portion of their financial resources to community empowerment programs. Their openness and willingness to collaborate facilitated constructive discussions, although their understanding of the SDGs framework remains limited. To bridge this gap, further data collection and analysis are required, focusing on key factors affecting land utilization based on SDGs principles. Moving forward, mentoring sessions aimed at formulating relevant policy recommendations and fostering stronger collaboration between the project team and village officials will be prioritized. These steps are essential to ensuring the success of the initiative and maintaining Yosowilangun's alignment with SDGs, while enhancing its development index.